High-impermeability silica sol-based grouting material and preparation method thereof
By adding nano calcium hydroxide and silane coupling agent to the silica sol, adjusting the pH value and adding calcium chloride solution, a high impermeability silicon sol-based grouting material is formed, which solves the problem of insufficient impermeability and compressive strength of existing materials, and achieves higher impermeability performance.
Patent Information
- Application Number
- CN202411698785.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-11
AI Technical Summary
The existing silicon sol-based grouting materials have shortcomings in terms of permeability and compressive strength, and it is difficult to meet the high-level anti-seepage requirements.
By adding nano calcium hydroxide and silane coupling agent to the silica sol, adjusting the pH value and adding a calcium chloride solution, a highly impermeable silica sol-based grouting material is formed.
The permeability and compressive strength of the silicon sol-based grouting material are significantly improved, with the permeability coefficient reaching 2.6×10-9~1.11×10-10cm/s, and the compressive strength reaching 0.55~0.70MPa.
Smart Images

Figure CN119591378A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an anti-seepage grouting material, in particular to a high-impermeability silica sol-based grouting material and a preparation method thereof. Background Art
[0002] As the country attaches great importance to pollution problems, the industry has put forward higher requirements for the anti-seepage standards of anti-seepage curtains. The "Design Code for Tailing Facilities" GB50863-2013 proposes that for the storage area of Class II general industrial solid waste and hazardous waste, the permeability coefficient should be set to no more than 1×10 -7 For tailings ponds with leakage problems that are in use or closed, it is unrealistic to remove the tailings in the pond and re-lay the horizontal anti-seepage system. Therefore, it is generally adopted to rebuild the vertical anti-seepage system around the pond area, and curtain grouting technology is the main measure to rebuild the vertical anti-seepage system.
[0003] Curtain grouting should achieve a permeability coefficient of less than 1×10 -7 The key to high-efficiency anti-seepage of cm / s lies in the research and development of grouting materials. At present, there are two common types of anti-seepage grouting materials: one is organic chemical slurry, such as acrylamide and polyurethane. Although they have good anti-seepage effect, their material cost is high and they have certain toxicity, so they are not widely used; the other is inorganic slurry materials, such as cement materials and water glass. Among them, cement-based materials have the advantages of low application cost and high mechanical strength of hardened body, but cement slurry contains a large number of solid particles, which is difficult to flow in nano-scale stratum cracks, so it cannot meet high-level anti-seepage requirements; water glass grouting material does not contain solid phase particles and has good injectability, but its gel time and strength are unstable. After curing, the gel dissolves more in water, resulting in insufficient volume stability and durability.
[0004] Nano-silica sol has received special attention in the field of grouting due to its good permeability, injectability and durability. However, single silica sol has problems such as poor solidification controllability, low solidified body strength and low impermeability in application, which greatly limits its practical application. Therefore, some researchers have improved its coagulation and solidification behavior by adding gelling agents and / or curing agents to silica sol. For example, Wei Kailun et al. investigated the effects of various salt solutions and acidity regulators on the coagulation time of silica sol and the compressive strength of the solidified sand body. The study found that when the KCl concentration was 7%, the silica gel ratio was 7:1 and the pH value was 7, the coagulation time of silica sol was about 14 minutes, the 3d compressive strength of the solidified sand body was 0.59 MPa, and the permeability coefficient of the silica sol solidified sand body after 28 days was 4.6×10 -7cm / s, the overall effect is still not ideal. This is because the surface of silica sol contains abundant hydroxyl groups and has high hydrophilicity. Water can easily pass through the cracks of the silica sol solid body, resulting in limited anti-penetration ability. So far, the permeability coefficient of the silica sol solid body is still difficult to exceed 1×10 -7 cm / s, which cannot meet the requirements for anti-seepage management of tailings ponds; in addition, the overall strength of silica sol grouting materials is low, the volume expansion rate is small under water conditions, and the volume shrinkage will occur under water loss conditions. After the dry-wet cycle of the formation, it may lead to anti-seepage failure; therefore, there is an urgent need to develop new modification technologies to obtain silica sol-based grouting materials with higher impermeability. Summary of the invention
[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a high-impermeability silica sol-based grouting material and a preparation method thereof, which has excellent impermeability and high compressive strength.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing a high-impermeability silica sol-based grouting material comprises the following steps:
[0008] Step 1, add 0.5-2.0 g of calcium hydroxide to 1 L of silica sol with a mass fraction of 30%-50%, stir well to obtain a uniform silica sol / calcium hydroxide solution;
[0009] Step 2, first taking a silane coupling agent according to 1% to 5% of the volume of the silica sol, and then mixing the silane coupling agent with a methanol solution with a mass fraction of 99.5% according to a volume ratio of the silane coupling agent to the methanol solution of 1: (2 to 5) to obtain a silane coupling agent alcohol solution;
[0010] Step 3, first add acid to the silica sol / calcium hydroxide solution, adjust the pH value of the silica sol / calcium hydroxide solution to weak acid or neutral, then add the silane coupling agent alcohol solution, mix evenly, and obtain component A; then, according to the volume ratio of silica sol to calcium chloride solution (6-10):1, take a calcium chloride solution with a mass fraction of 5%-10% and add it to component A, stir evenly, and obtain a high impermeability silica sol-based grouting material.
[0011] Furthermore, the average particle size of the calcium hydroxide in step 1 is 10 to 100 nm.
[0012] Furthermore, the silane coupling agent in step 2 is dodecyltrimethoxysilane, dodecyltriethoxysilane or dodecyldimethylchlorosilane.
[0013] Furthermore, the acid solution in step 3 is an acetic acid solution with a mass fraction of 97% to 99.8%.
[0014] Furthermore, in step 3, the pH value of the silica sol / calcium hydroxide solution is adjusted to 5-7.
[0015] Furthermore, in step 3, the viscosity of component A is 5 to 7 mPa·s, the viscosity of the calcium chloride solution is 0.3 to 0.6 mPa·s, and the initial viscosity of the high-impermeability silica sol-based grouting material is 4 to 6 mPa·s.
[0016] A highly impermeable silica sol-based grouting material.
[0017] Furthermore, the permeability coefficient of the silica sol-based grouting material solidified sand body formed by the high-impermeability silica sol-based grouting material and sand is 2.6×10 -9 ~1.11×10 -10 cm / s.
[0018] Furthermore, the compressive strength of the silica sol-based grouting material solidified sand body formed by the high-impermeability silica sol-based grouting material and sand after curing for 28 days is 0.55 to 0.70 MPa.
[0019] Compared with the prior art, the present invention has the following technical effects:
[0020] On the one hand, considering that nano calcium hydroxide is uniformly dispersed in silica sol without precipitation, it has little effect on the viscosity and injectability of silica sol. Therefore, nano calcium hydroxide is uniformly dispersed in silica sol. Nano calcium hydroxide reacts chemically with silica sol to generate hydrated calcium silicate gel, and reacts with carbon dioxide in the air to generate calcium carbonate. Hydrated calcium silicate gel and calcium carbonate can be filled in the pores of the solidified body, effectively improving the density of the silica sol solidified body, and improving its impermeability and compressive strength. On the other hand, when a silane coupling agent alcohol solution is added to the silica sol, the hydrolyzed group of the coupling agent bonds with the silicon oxide in the silica sol, and the long hydrophobic carbon chain can be modified on the surface of the silicon oxide, so that the hydrophobicity of the silica sol is enhanced, thereby significantly improving the impermeability of the silica sol-based grouting material. On the other hand, after adding acid and calcium chloride solution to the material system, the number of negative charges on the surface of the silicon oxide particles is reduced, and at the same time, Ca 2+ The ions are adsorbed to the surface of the particles, the particles continue to aggregate, and the hydroxyl groups on the surface of the particles undergo polymerization reactions, and the viscosity of the system increases slowly. As more and more particles aggregate, a large number of particles undergo dehydration and cross-linking reactions to form a network polymer. The viscosity of the system increases rapidly and condensation and solidification occur. In addition, calcium chloride can react with OH in the solution. - The silica sol-based grouting material prepared by the present invention and the sand-solidified body formed by the sand have a permeability coefficient of up to 2.6×10 -9 ~1.11×10 -10cm / s, and the compressive strength can reach 0.55-0.70MPa after 28 days of curing.
[0021] The raw materials used in preparing the high-impermeability silica sol-based grouting material according to the present invention are cheap and easily available, the preparation process does not involve harmful substances, is environmentally friendly, and the preparation process is simple and easy. The prepared silica sol-based grouting material has excellent impermeability and has extremely high market application prospects in the field of high-level anti-seepage grouting. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 : Curve of the viscosity of the high impermeability silica sol-based grouting material prepared in Example 1 of the present invention changing with time;
[0023] Figure 2 : XRD spectrum of the high impermeability silica sol-based grouting material prepared in Example 1 of the present invention;
[0024] Figure 3 : FTIR spectrum of the high impermeability silica sol-based grouting material prepared in Example 1 of the present invention;
[0025] Figure 4 : Water drop contact angle of commercially available silica sol and the high impermeability silica sol-based grouting material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0026] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.
[0027] The mass fraction of the acetic acid solution selected in Examples 1 to 22 is 97% to 99.8%.
[0028] The average particle size of the calcium hydroxide selected in Examples 1 to 22 is 10 to 100 nm.
[0029] Example 1
[0030] Step 1, add 1.43g of calcium hydroxide to 1L of 40% silica sol, stir for 4h to obtain a uniform silica sol / calcium hydroxide solution;
[0031] Step 2, taking 50 mL of dodecyltrimethoxysilane and 150 mL of a 99.5% by mass methanol solution and mixing them to obtain a silane coupling agent alcohol solution;
[0032] Step 3: first add acetic acid solution to the silica sol / calcium hydroxide solution, adjust the pH value to 7, then add the silane coupling agent alcohol solution, mix well to obtain component A, and then add 8% by mass calcium chloride solution to component A according to the volume ratio of silica sol to calcium chloride solution of 7:1, stir well to obtain a high impermeability silica sol-based grouting material.
[0033] The viscosity of component A prepared in Example 1 is 4.41 mPa·s, the viscosity of the selected calcium chloride solution is 0.49 mPa·s, and the initial viscosity of the prepared high-impermeability silica sol-based grouting material is 4.87 mPa·s. Figure 1 The viscosity of the high-impermeability silica sol-based grouting material increases with time. At 40 minutes, the viscosity is 24 mPa·s, which has good injectability. At 60 minutes, the viscosity is 488 mPa·s, and the slurry basically does not flow, indicating that the high-impermeability silica sol-based grouting material prepared in Example 1 can solidify after 60 minutes.
[0034] After the high impermeability silica sol-based grouting material prepared in Example 1 was dried, it was characterized and analyzed by XRD and FTIR. Figure 2 From the XRD spectrum, it can be seen that the mantou peak at about 22° in the XRD spectrum of the silica sol grouting material powder sample corresponds to amorphous silicon oxide, the characteristic peaks at about 31.5° and 45.3° are the characteristic peaks of calcium chloride crystals, and weak characteristic peaks of calcium hydroxide appear at 18.1°, 34.2° and 50.6°. Figure 3 From the FTIR spectrum, we can see that at 2927cm -1 and 2857cm -1 An obvious -CH2 bending vibration peak appears at the , which is caused by the presence of coupling agent in the sample. The hydrolyzed groups of the coupling agent bond with the silicon oxide in the silica sol, and the long hydrophobic carbon chain can be modified on the silicon oxide surface, which enhances the hydrophobicity of the silica sol and thus improves the impermeability of the silica sol-based grouting material.
[0035] After the dried silica sol-based grouting material powder was pressed into a tablet, the water drop contact angle was tested. The results are as follows: Figure 4 As shown, it was found that the water droplet contact angle of the sample was 68°, which had a certain hydrophobicity; under the same conditions, the commercially available silica sol without the addition of calcium hydroxide and silane coupling agent alcohol solution was dried and pressed into sheets, and the water droplet contact angle was tested. The water droplet contact angle was almost 0°, indicating that the silica sol-based grouting material prepared in Example 1 had better impermeability than the commercially available silica sol.
[0036] Example 2 to Example 22
[0037] The preparation method is the same as that of Example 1, except that the specific raw materials used, the ratio of the raw materials and other parameters are different, see Table 1 for details.
[0038] Table 1: Raw material ratios of Example 2 to Example 22
[0039]
[0040]
[0041] The high-impermeability silica sol-based grouting materials prepared in Examples 1 to 22 were respectively poured into a mold with a diameter of 90 mm and a height of 35 mm filled with standard sand, so that the slurry formed a solid sand body in the mold, and the top of the test mold was covered with a plastic wrap. After standard curing for 28 days, water was injected from the bottom of the solid sand body using an SS-15 mortar permeameter to allow water to pass through the silica sol solid sand body sample. When water flowed out of the drain port, the maximum pressure (H1) and minimum pressure (H2) and the starting time on the instrument panel of the mortar permeameter were recorded, the overflowed water was collected, the duration (t) was recorded, and the amount of water collected (Q) was measured to test the permeability coefficient of the sample. The results are shown in Table 2.
[0042] A detachable thickened plastic ABS test mold with a diameter of 50 mm and a height of 100 mm was used to cast the sand consolidation body. The specific test process was as follows: the uniformly mixed standard sand was poured into the mold installed in advance, and the high impermeability silica sol-based grouting materials prepared in Examples 1 to 22 were respectively injected into the standard sand until the liquid overflowed from the surface, and the injection was stopped. Then, a small amount of standard sand was added to grind the surface flat, and the upper surface was tightly wrapped with plastic wrap. After curing at room temperature for 28 days, the mold was demoulded and the strength was tested using a universal testing machine. The results are shown in Table 2;
[0043] Table 2 Permeability coefficient and compressive strength of silica sol sand consolidation body
[0044]
Claims
1. A method for preparing a high-impermeability silica sol-based grouting material, characterized in that: The steps include: Step 1, adding 0.5-2.0 g of nano calcium hydroxide into 1 L of silica sol with a mass fraction of 30%-50%, stirring thoroughly to obtain a uniform silica sol / calcium hydroxide solution; Step 2, first taking a silane coupling agent according to 1% to 5% of the volume of the silica sol, and then mixing the silane coupling agent with a methanol solution with a mass fraction of 99.5% according to a volume ratio of the silane coupling agent to the methanol solution of 1: (2 to 5) to obtain a silane coupling agent alcohol solution; Step 3, first add acid to the silica sol / calcium hydroxide solution, adjust the pH value of the silica sol / calcium hydroxide solution to weak acid or neutral, then add the silane coupling agent alcohol solution, mix evenly, and obtain component A; then, according to the volume ratio of silica sol to calcium chloride solution (6-10):1, take a calcium chloride solution with a mass fraction of 5%-10% and add it to component A, stir evenly, and obtain a high impermeability silica sol-based grouting material.
2. The method for preparing a high-impermeability silica sol-based grouting material according to claim 1, characterized in that: The average particle size of the nano calcium hydroxide in step 1 is 10 to 100 nm.
3. The method for preparing a high-impermeability silica sol-based grouting material according to claim 1, characterized in that: The silane coupling agent in step 2 is dodecyltrimethoxysilane, dodecyltriethoxysilane or dodecyldimethylchlorosilane.
4. The method for preparing a high-impermeability silica sol-based grouting material according to claim 1, characterized in that: The acid solution in step 3 is an acetic acid solution with a mass fraction of 97% to 99.8%.
5. The method for preparing a high-impermeability silica sol-based grouting material according to claim 1, characterized in that: In step 3, the pH value of the silica sol / calcium hydroxide solution is adjusted to 5-7.
6. The method for preparing a high-impermeability silica sol-based grouting material according to claim 1, characterized in that: In the step 3, the viscosity of component A is 5-7 mPa·s, the viscosity of the calcium chloride solution is 0.3-0.6 mPa·s, and the initial viscosity of the high-impermeability silica sol-based grouting material is 4-6 mPa·s.
7. A high-impermeability silica sol-based grouting material prepared by the method according to any one of claims 1 to 6.
8. The high impermeability silica sol-based grouting material according to claim 7, characterized in that: The permeability coefficient of the sand-solidified body formed by the silica sol-based grouting material and sand is 2.6×10 -9 ~1.11×10 -10 cm / s.
9. The high impermeability silica sol-based grouting material according to claim 7, characterized in that: The compressive strength of the sand body formed by the silica sol-based grouting material and sand after 28 days of curing is 0.55-0.70 MPa.